Pendidikan Kesehatan Kepada Keluarga “Perawatan Luka Pasca Khitan Metode Konvensional Yang Optimal” - A Firmansyah; Henri Setiawan; Suhanda Suhanda; A Fitriani; E Roslianti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2018)
Community service aims to increase family knowledge and understanding of signs and symptoms of post-circumcision wounds, teach how to care for wounds to heal quickly and provide an understanding of things that must be done and avoided in post-circumcision children. Health counseling methods provided through lectures using the help of leaflets. Community Service The optimal post-circumcision wound care method that is optimal is followed by 104 parents of children who are mass circumcised and given counseling privately to individuals when waiting for their children to be circumcised. Activities included filling in data on children who were circumcised and coming to the da'wah building of Sukanagara Village, Kec. Lakbok on December 2, 2018, which was subsequently conducted by a person's health education by 5 counselors using the help of a leaflet.